Astrocyte-derived exosomes regulate sperm miR-34c levels to mediate the transgenerational effects of paternal chronic social instability stress - Alexandre Champroux; Mitra Sadat-Shirazi; Xuan Chen; Jonathan Hacker; Yongjie Yang; Larry A. Feig (Epigenetics)
The effects of chronically stressing male mice can be transmitted across generations by stress-specific changes in their sperm miRNA content, which induce stress-specific phenotypes in their offspring. However, how each stress paradigm alters the levels of distinct sets of sperm miRNAs is not known. We showed previously that exposure of male mice to chronic social instability (CSI) stress results in elevated anxiety and reduced sociability specifically in their female offspring across multiple generations because it reduces miR-34c levels in sperm of stressed males and their unstressed male offspring. Here, we describe evidence that astrocyte-derived exosomes (A-Exos) carrying miR-34c mediate how CSI stress has this transgenerational effect on sperm. We found that CSI stress decreases miR-34c carried by A-Exos in the prefrontal cortex and amygdala, as well as in the blood of males. Importantly, miR-34c A-Exos levels are also reduced in these tissues in their F1 male offspring, who despite not being exposed to stress, exhibit reduced sperm miR-34c levels and transmit the same stress-associated traits to their male and female offspring. Furthermore, restoring A-Exos miR-34c content in the blood of CSI-stressed males by intravenous injection of miR-34c-containing A-Exos restores miR-34c levels in their sperm. These findings reveal an unexpected role for A-Exos in maintaining sperm miR-34c levels by a process that when suppressed by CSI stress mediates this example of transgenerational epigenetic inheritance.